The Development Of Malaysian University Choir : A Case Study On Current Choral Practice From The Perspectives Of Choir Members - Dayang Siti Aishah, Awang Matali; Thia, Sock Siang (The International Journal of Innovative Design, Creativity and Social Sciences (IJIDeCS), 2018)
The purpose of this study was to study the development of Malaysian university choirs. Specifically, this study focused on current choral practice from the perspectives of choir members. Although the number of university choirs has multiplied over the past twenty years due to the increased tertiary music programs being offered in Malaysia, very few studies have been conducted from the choir members’ perspective, especially in the Malaysian context. In seeking greater understanding, this study was conducted using quantitative method.Questionnaire was distributed to choir members from selected universities to gain insight into their experiences with the choirs, to discuss the challenges they faced, and to seek strategies in improving the overall quality of the choir. As a result, all choir members acknowledged the importance of choral activities. Financial constraint was the most crucial challenge faced by the choir groups. Besides, greater opportunities to get involved in performances and competitions especially outside Malaysia was essential to ensure a better standard of the choir as a whole. A lot of talents are supposed to be seen and assisted as they are also contributing to the good reputation of a university as well as a country. Financial problem should not be an obstacle to the development of choir in Malaysia. Therefore, this study provides a better understanding about the development of university choirs in Malaysia by looking at the choir members’ experience, identifying challenges faced by them, and formulate possible strategies in order to raise the overall standard of university choirs in Malaysia.